Structural degradation of community-managed mangroves under illegal logging pressure in Lubuk Kertang, North Sumatra, Indonesia - ONRIZAL ONRIZAL; DEBORA RATUA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Onrizal, Ratua D. 2026. Structural degradation of community-managed mangroves under illegal logging pressure in Lubuk Kertang, North Sumatra, Indonesia. Biodiversitas 27 (4): d270440. https://doi.org/10.13057/biodiv/d270440. Illegal logging is a major pressure on mangrove ecosystems, but field-based evidence that links ecological condition with community perception remains limited in Indonesia. This study assessed whether mangrove structure and health differed between two stations with contrasting disturbance levels in Lubuk Kertang Village, North Sumatra, and how local people perceived current mangrove condition and management priorities. Vegetation was sampled in nested seedling, sapling, and tree plots along two 300-m transects, and community structure, importance value index, and Mangrove Health Index (MHI) were calculated. Perceptions were analyzed from an 11-item Likert questionnaire administered to 52 respondents. Ecological differences between stations were evaluated using independent t-tests or Mann-Whitney U tests, depending on data distribution. Station I contained seven species and showed moderate condition (MHI 56.27%), whereas Station II contained six species and showed poor condition (MHI 32.95%). The disturbed station had significantly lower canopy cover, tree density, seedling abundance, basal area, mean stem diameter, and mean height, while felled stands occurred only at that station. Respondents strongly acknowledged mangrove benefits, recognized ongoing degradation, and supported stricter supervision, sanctions, and rehabilitation. Taken together, the results indicate that illegal logging in Lubuk Kertang is associated more strongly with structural degradation than with immediate local species loss. These findings support two near-term management priorities: stronger protection of remaining higher-integrity stands and hydrology-informed restoration of degraded and abandoned-pond areas.